Safety and Efficacy Study of the Cyclooxygenase‐2 Inhibitor Parecoxib Sodium Applied for Postoperative Analgesia After Endo‐Nasal Operation. Issue 4 (10th April 2015) - Chen, Hong; Luo, Ailin
Abstract: Objective: To evaluate the safety and efficacy of the cyclooxygenase‐2 inhibitor parecoxib sodium after endo‐nasal operation. Methods: Patients aged 18 to 55 years with body mass index (BMI) ≤25 and ASAI~II who were undergoing endo‐nasal operation were randomly allocated to receive either IV parecoxib sodium 40 mg or IV placebo (saline) 2 mL 15 minutes before induction of anesthesia. The magnitude of pain was measured using the visual analogue scale (VAS) and recorded on awakening, then at interval of 1, 2, 4, 6, 8, 12, and 24 hours after operation. Safety evaluation including nausea, vomiting, dry mouth, drowsiness, urinary retention, respiratory depression, surgical site bleeding, and so on was assessed. The patients' satisfaction of the postoperative analgesia was recorded and compared between the 2 groups. Results: A total of 64 patients were enrolled in the study, including 31 in parecoxib group and 33 in placebo group. The VAS scores at 1, 2, 4, 6, 8 hours after operation were significantly lower in parecoxib group than in placebo group ( P  <   0.05). The P values were 0.002, <0.001, 0.001 at 2, 4, 6 hours after operation, respectively. The percentage of the patients who considered the postoperative analgesia "good" or "excellent" was 45.2% in parecoxib group and 9.1% in placebo group. There were no serious side effects in both groups. Conclusions: Parecoxib sodium was effective and safe when used for postoperative analgesia in endo‐nasal operation.